The BecA-ILRI Hub and its contribution to African agricultural biotechnology and crop improvement - Djikeng, Appolinaire (KSIConnect, 2015)
5th International Conference on Next Generation Genomics and Integrated Breeding for Crop Improvement, ICRISAT, Patancheru, India, 18-20 February 2015